2017
DOI: 10.7860/jcdr/2017/27027.10174
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Diabetic Retinopathy: Knowledge, Attitude, Practice (Kap ) among Diabetic Patients in A Tertiary Eye Care Centre

Abstract: Introduction: Diabetic retinopathy is becoming an increasingly important cause of visual impairment in India. Many diabetic patients who come to our centre have undetected, advanced diabetic retinopathy. If diabetic retinopathy had been detected earlier in these patients, irreversible visual impairment could have been prevented. Aim:To document Knowledge, Attitude and Practice (KAP) patterns of diabetic patients regarding diabetes and diabetic retinopathy, to determine association between them, and to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
91
4
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(110 citation statements)
references
References 13 publications
13
91
4
2
Order By: Relevance
“…Regarding mean score of knowledge of the studied population; 5.34±1.0 in pre-test, which indicated poor knowledge, improved in post-test to 16.66±1.8, this result was similar to that of Srinivasan NK et al, 16 who observed that only 4.5% of studied sample had good knowledge about retinopathy. Also, Geethadevi M et al 30 found that 60.8% had no knowledge of diabetic retinopathy and Panigrahi S et al 31 reported that 69.0% of the study population had poor knowledge of diabetic retinopathy.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Regarding mean score of knowledge of the studied population; 5.34±1.0 in pre-test, which indicated poor knowledge, improved in post-test to 16.66±1.8, this result was similar to that of Srinivasan NK et al, 16 who observed that only 4.5% of studied sample had good knowledge about retinopathy. Also, Geethadevi M et al 30 found that 60.8% had no knowledge of diabetic retinopathy and Panigrahi S et al 31 reported that 69.0% of the study population had poor knowledge of diabetic retinopathy.…”
Section: Discussionsupporting
confidence: 86%
“…A few studies have been conducted regarding the knowledge and awareness about DR among the diabetic population. 16 This is the first study carried out on knowledge, attitude, and practice regarding DR in Assuit university hospital. So, the current study has been conducted to determine the level of knowledge, attitude, reported practice, and to identify the impact of an educational program on a diabetic population.…”
Section: Introductionmentioning
confidence: 99%
“…16 Mahesh G et al and Srinivasan N K et al, also found a statistically significant association between awareness of diabetic retinopathy and good practice patterns regarding retinopathy in their studies. 19,20 In primary health centres, physicians can play a major role in creating awareness and imparting knowledge about diabetic retinopathy. Data from our study also reflects this.…”
Section: Discussionmentioning
confidence: 99%
“…Similar reasons were given by patients in studies done in Vellore [1] and Jordan. [11] As no similar studies were previously done in our setting, this provides information toward an understanding of health seeking behavior of diabetics regarding one of the major causes of blindness in this populace.…”
Section: Discussionmentioning
confidence: 61%
“…[9] This awareness was low as compared to studies done in Vellore (71.9%) [1] , Nepal (63.3%), [10] and Jordan (98.3%). [11] Majority of the patients 83.3% believed that individuals with controlled diabetes will have no eye problem which is higher as compared to the findings done in Bagalkot (68%) [2] and Malaysia (51.1%).…”
Section: Discussionmentioning
confidence: 96%